Effects of Bilingualism on Reading Fluency: An Analysis of Pausing Patterns of Iranian Learners of English as a Third Language. (24th November 2021) - Banitalebi, Zahra; Jabbari, Ali Akbar; Tilwani, Shouket Ahmad; Razmi, Mohammad Hasan
Abstract : Fluency is one of the most important components of oral proficiency, which can be affected by a number of variables including frequency, duration, and place of pause phenomena. The present study aimed at investigating the effect of bilingualism on learning a foreign language from the angle of fluency and pausing patterns by comparing the pausing patterns of monolingual (Persian speakers) and bilingual (Iranian Turkish speakers; L1: Turkish and L2: Persian) EFL learners. To this end, a sample of 40 male and female advanced EFL learners were selected from Yazd University and several English-language institutes. An English reading passage test was used to measure students' fluency in terms of their pausing patterns in prepared mode of speech. As learners started to read the passage, their speeches were recorded. The collected data were analyzed by Praat software. The statistical analyses revealed a significant difference between monolingual and bilingual learners in the frequency, duration, and placement of the pauses they had produced while they were reading the English passage. The results showed that bilingual learners outperformed monolingual participants, suggesting the superiority of bilinguals in their pausing patterns. The implications are discussed.